2011
DOI: 10.1007/s00405-011-1790-9
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis: some aspects of laterality in 326 patients

Abstract: Lateralization of primary epistaxis was prospectively studied in 326 patients at Radebeul Elblandklinikum. The male-female-ratio was 1.3:1. A slight dominance of the right side (45% right vs. 39% left) was found in all patients. Further analyzed were the relationship to the localization of bleeding (anterior or posterior), the age and possible causes or risk factors. Nose bleeding from the posterior nasal portion appears to be statistically significantly higher than on both sides of anterior epistaxis. No stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
1
0
1
Order By: Relevance
“…There is a belief that in 85% of the cases of epistaxis, there is no identifiable cause [26]. Contrary to this belief, our study and several others reported that there is a proven cause of epistaxis in considerable percentages of their studied sample [12,25,27].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…There is a belief that in 85% of the cases of epistaxis, there is no identifiable cause [26]. Contrary to this belief, our study and several others reported that there is a proven cause of epistaxis in considerable percentages of their studied sample [12,25,27].…”
Section: Discussioncontrasting
confidence: 95%
“…Send et al reported that anterior epistaxis was encountered in 76.7% of their cases [21]. Another study from Germany also reported that anterior epistaxis (85%) was more prevalent than posterior (13%) [25]. Our study revealed that the vast majority of the cases were had anterior epistaxis (97.1%).…”
Section: Discussionsupporting
confidence: 55%